Adhesive sheet for battery and lithium-ion battery

By using inorganic particles with low moisture content, such as barium sulfate particles, in the adhesive layer of the battery adhesive sheet, the problem of gas generation and insulation of the battery adhesive sheet in high temperature environments is solved, and the safety and performance of the battery are improved.

CN113046002BActive Publication Date: 2025-01-24LINTEC CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202011550950.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-26
Filing Date
2020-12-24
Publication Date
2025-01-24
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

The existing battery adhesive sheet is prone to gas in high temperature environments, causing the battery to expand, and it is difficult to maintain high insulation and low cost at the same time.

Method used

An adhesive sheet for batteries using a base material and an adhesive layer, wherein the adhesive layer contains inorganic particles with a moisture content of 0.4% or less in monomer form, preferably sulfate particles, such as barium sulfate particles.

Benefits of technology

Even in high-temperature environments, gas is not easily generated, thereby suppressing battery expansion, maintaining high insulation, and improving battery safety and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113046002B_ABST
    Figure CN113046002B_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet for a battery that is not prone to generate gas even when placed in a high temperature environment, and a lithium ion battery using the adhesive sheet for a battery. The adhesive sheet for a battery is an adhesive sheet for a battery (1) having a substrate (11) and an adhesive layer (12) disposed on one side of the substrate (11), wherein the adhesive layer (12) contains inorganic fine particles (121) having a water content of 0.4% or less when in a single state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive sheet for a battery and a lithium ion battery manufactured using the adhesive sheet for a battery. Background Art

[0002] In some batteries, a strip-shaped stack composed of a positive electrode, a negative electrode, and a separator therebetween is wound and stored inside. The positive electrode and the negative electrode are each connected to an electrode extraction tab formed of a conductor, and the positive electrode and the negative electrode are electrically connected to the positive terminal and the negative terminal of the battery, respectively, through these electrode extraction tabs.

[0003] An adhesive sheet is sometimes used for the winding and fixing of the above-mentioned stack or the fixing of the electrode extraction tab on the electrode. As such an adhesive sheet, an adhesive sheet formed by a substrate and an adhesive layer provided on one surface of the substrate is generally used. In addition, from the perspective of improving the required performance of insulation, an adhesive sheet is sometimes used in which an insulating layer containing an insulating material is provided on the surface of the substrate opposite to the adhesive layer or between the substrate and the adhesive layer.

[0004] However, separately providing the above-mentioned insulating layer and adhesive layer will lead to an increase in manufacturing costs. Therefore, people have also tried to improve the insulation of the adhesive sheet by including an insulating material in the adhesive layer without providing the above-mentioned insulating layer. For example, in Patent Document 1, an adhesive sheet containing aluminum oxide in the adhesive layer is disclosed. In addition, in Patent Document 2, an adhesive sheet containing magnesium hydroxide, aluminum oxide, magnesium oxide, aluminum hydroxide, silicon dioxide, boron nitride, titanium oxide or magnesium carbonate in the adhesive layer is disclosed.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2017 / 038010

[0008] Patent Document 2: Japanese Patent Application Publication No. 2017-152372 Summary of the invention

[0009] Technical Problems to be Solved by the Invention

[0010] However, in recent years, from the perspective of improving the safety of the battery and enabling the battery to maintain its performance well, it is required that the properties or characteristics of the adhesive sheet be maintained even when the battery is placed in a high temperature environment. In particular, it is required that even if the battery is placed in a high temperature environment, gas is not released from the adhesive sheet, thereby suppressing the expansion of the battery caused by the release of the gas. Therefore, it is expected to develop a battery adhesive sheet that can meet this demand at a higher level.

[0011] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide an adhesive sheet for a battery that is unlikely to generate gas even when placed in a high-temperature environment, and a lithium ion battery using the adhesive sheet for a battery.

[0012] Technical means to solve technical problems

[0013] To achieve the above object, first, the present invention provides an adhesive sheet for a battery comprising a substrate and an adhesive layer provided on one surface of the substrate, wherein the adhesive layer contains inorganic fine particles having a water content of 0.4% or less in a single state (Invention 1).

[0014] The adhesive sheet for a battery of the invention (Invention 1) described above contains inorganic fine particles having the above-mentioned water content in the adhesive layer, so that gas is not easily generated even when placed in a high-temperature environment. Therefore, by using the adhesive sheet for a battery, a battery exhibiting excellent performance can be manufactured.

[0015] In the above invention (Invention 1), it is preferred that the inorganic fine particles are sulfate fine particles (Invention 2).

[0016] In the above invention (Invention 2), it is preferred that the sulfate fine particles are barium sulfate fine particles (Invention 3).

[0017] In the above inventions (Inventions 1 to 3), preferably, the content of the inorganic fine particles in the adhesive layer is 5 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the adhesive component contained in the adhesive layer (Invention 4).

[0018] In the above inventions (Inventions 1 to 3), it is preferred that the average particle size of the inorganic fine particles is 0.01 μm or more and 10 μm or less (Invention 5).

[0019] Second, the present invention provides a lithium ion battery characterized in that two or more conductors are fixed in contact with each other inside the battery using the adhesive sheet for a battery (Inventions 1 to 5) (Invention 6).

[0020] Effects of the Invention

[0021] The adhesive sheet for a battery of the present invention is unlikely to generate gas even when placed in a high temperature environment. Therefore, a lithium ion battery manufactured using the adhesive sheet for a battery can exhibit excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a cross-sectional view of an adhesive sheet for a battery according to one embodiment of the present invention.

[0023] Figure 2This is a partially exploded perspective view of a lithium ion battery according to one embodiment of the present invention.

[0024] Figure 3 This is an exploded perspective view of an electrode body of a lithium ion battery according to one embodiment of the present invention.

[0025] Description of Reference Numerals

[0026] 1: Adhesive sheet for battery; 11: Base material; 12: Adhesive layer; 121: Inorganic particles; 13: Release sheet; 2: Lithium-ion battery; 21: Outer casing; 22: Positive terminal; 23: Negative terminal; 24: Electrode body; 241: Positive current collector; 241a: Positive active material layer; 242: Negative current collector; 242a: Negative active material layer; 243: Separator; 244: Electrode extraction tab. DETAILED DESCRIPTION

[0027] Hereinafter, embodiments of the present invention will be described.

[0028] [Adhesive sheet for batteries]

[0029] like Figure 1 As shown, an adhesive sheet 1 for a battery according to an embodiment of the present invention comprises a substrate 11, an adhesive layer 12 provided on one surface side of the substrate 11, and a release sheet 13 provided on the surface side of the adhesive layer 12 opposite to the substrate 11. In the adhesive sheet 1 for a battery according to the present embodiment, the adhesive layer 12 contains inorganic fine particles 121.

[0030] Here, the "battery adhesive sheet" in this specification is an adhesive sheet used in a position that may come into contact with an electrolyte during battery manufacturing, preferably an adhesive sheet used inside a battery, or an adhesive sheet for battery interior installation. As a battery, a non-aqueous battery is preferred. Therefore, the electrolyte used in the battery is preferably a non-aqueous electrolyte. The battery adhesive sheet in this specification is preferably an adhesive sheet attached to a portion inside a non-aqueous battery that may be immersed in an electrolyte or a portion that may come into contact with an electrolyte. As a non-aqueous battery, a lithium ion battery is particularly preferred.

[0031] 1. Each component

[0032] 1-1. Base material

[0033] In the battery adhesive sheet 1 of the present embodiment, the minimum voltage at which insulation breakdown occurs is preferably high for the substrate 11. For example, the voltage is preferably 1 kV or more, particularly preferably 2 kV or more, and further preferably 5 kV or more. By setting the voltage to 1 kV or more, insulation breakdown of the substrate 11 is less likely to occur, and the reliability of the battery adhesive sheet 1 becomes higher.

[0034] Furthermore, the substrate 11 preferably has a flame retardancy that satisfies the flame retardancy grade V-0 of the UL94 standard. By providing the substrate 11 with such flame retardancy, even when heat is generated by normal use of the battery, the modification or deformation of the substrate 11 can be suppressed. In addition, even when a battery malfunctions or excessive heat is generated, the ignition or combustion of the substrate 11 can be suppressed, thereby preventing serious accidents.

[0035] The material of the substrate 11 can be appropriately selected from the viewpoints of insulation, flame retardancy, heat resistance, reactivity with the electrolyte, permeability of the electrolyte, etc. In particular, a resin film is preferably used as the substrate 11 . Examples of the resin film include polyester films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polyolefin films such as polyethylene films and polypropylene films, films formed from polymers containing nitrogen in the main chain such as polyamide films, polyimide films, and polyamideimide films, cellophane, cellulose diacetate films, cellulose triacetate films, cellulose acetate butyrate films, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene-vinyl acetate copolymer films, polystyrene films, polycarbonate films, polymethylpentene films, polysulfone films, polyetheretherketone films, polyethersulfone films, polyetherimide films, fluororesin films, acrylic resin films, polyurethane resin films, norbornene polymer films, cyclic olefin polymer films, cyclic conjugated diene polymer films, vinyl alicyclic hydrocarbon polymer films, and other resin films or laminated films thereof. In particular, from the perspective of insulation and flame retardancy, films of polymers containing nitrogen in the main chain are preferred (they may also contain components other than the polymer. The same applies in this specification), films of polymers having a nitrogen-containing ring structure in the main chain are particularly preferred, and films of polymers having a nitrogen-containing ring structure and an aromatic ring structure in the main chain are further preferred. Specifically, for example, polyimide films, polyetherimide films, or polyetheretherketone films are preferred, and polyimide films having particularly excellent insulation and flame retardancy are preferred.

[0036] The lower limit of the thickness of the substrate 11 is preferably 5 μm or more, particularly preferably 10 μm or more, and further preferably 15 μm or more. By setting the lower limit of the thickness of the substrate 11 to the above value, for example, even when the electrode body formed by fixing the electrode and removing the tab using the battery adhesive sheet 1 is wound and the winding pressure is applied to the battery adhesive sheet 1, the breakage of the substrate 11 can be effectively suppressed. In addition, the upper limit of the thickness of the substrate 11 is preferably 200 μm or less, particularly preferably 100 μm or less, and further preferably 40 μm or less. By setting the upper limit of the thickness of the substrate 11 to the above value, the battery adhesive sheet 1 has moderate flexibility, and even when the battery adhesive sheet 1 is attached to the surface with a step difference, such as when fixing the electrode and the electrode removing the tab, the step difference can be well followed.

[0037] 1-2. Adhesive layer

[0038] (1) Inorganic particles

[0039] The adhesive layer 12 contains an adhesive component and inorganic fine particles 121. The adhesive layer 12 contains the inorganic fine particles 121, so that the adhesive layer 12 functions as an insulating layer. Therefore, the adhesive sheet 1 for a battery of the present embodiment has excellent insulating properties.

[0040] Furthermore, the inorganic fine particles 121 in the present embodiment have a water content of 0.4% or less when used alone. By making the water content 0.4% or less, when the battery adhesive sheet 1 is heated, the generation of gas from the adhesive layer 12 can be well suppressed. Therefore, using the battery adhesive sheet 1 of the present embodiment, a battery that is not easily expanded due to the generation of the above-mentioned gas can be manufactured. From this perspective, the above-mentioned water content is preferably 0.3% or less, and particularly preferably 0.2% or less.

[0041] The lower limit of the water content is not particularly limited, and may be, for example, 0% or more, particularly 0.01% or more, and further 0.05% or more.

[0042] In addition, the water content of the inorganic particles 121 in this specification refers to the water content measured for the inorganic particles 121 as a single body, and is neither the water content of the inorganic particles 121 in the adhesive layer 12 nor the water content of the inorganic particles 121 in the adhesive composition P described later. In addition, the water content of the inorganic particles 121 in this specification refers to the water content measured by the Karl Fischer method, and the water measured here is attached to the inorganic particles 121 in a form other than covalent bonding with the inorganic particles 121. The details of the method for measuring the water content of the inorganic particles 121 are shown in the description of the test examples described later.

[0043] As the inorganic particles 121 in the present embodiment, as long as they have the above-mentioned water content, there is no particular limitation, and barium sulfate, titanium dioxide, aluminum hydroxide, sodium sulfate, sodium bisulfate, potassium sulfate, magnesium sulfate, calcium sulfate, magnesia (magnesium oxide), aluminum oxide, calcium carbonate, silicon dioxide, boehmite, talc, iron oxide, silicon carbide, boron nitride, zirconium oxide, magnesium hydroxide, magnesium carbonate, aluminum nitride and other powders, beads sphericalized from these powders, single crystal fibers and glass fibers, etc. can be used. These particles can be used alone, or two or more can be mixed and used. Among them, from the perspective of being easy to achieve the above-mentioned water content, it is preferred to use at least one of barium sulfate, titanium dioxide and aluminum hydroxide.

[0044] In addition, from the perspective of achieving better insulation, sulfate particles are preferably used as inorganic particles 121. By using sulfate particles, in a battery using the battery adhesive sheet 1 of the present embodiment, even if an internal short circuit occurs due to the mixing of foreign matter in the battery, it is easy to suppress the heat caused by the internal short circuit. As a result, the battery adhesive sheet 1 of the present embodiment is easy to exert better insulation. As examples of such sulfate particles, powders of barium sulfate, sodium sulfate, sodium hydrogen sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, etc., beads formed by sphericalizing these powders, single crystal fibers and glass fibers, etc. can be listed. Among them, from the perspective of high chemical stability and good dispersibility with adhesive components, barium sulfate particles are preferably used.

[0045] The average particle size of the inorganic particles 121 is preferably 0.01 μm or more, particularly preferably 0.1 μm or more, further preferably 0.2 μm or more, and most preferably 0.4 μm or more. In addition, the average particle size of the inorganic particles 121 is preferably 10 μm or less, particularly preferably 5 μm or less, and further preferably 0.9 μm or less. By making the average particle size of the inorganic particles 121 to be 0.01 μm or more, it is easy to achieve the above-mentioned moisture content, and the battery adhesive sheet 1 of this embodiment is easy to exert high insulation. Furthermore, by making the average particle size of the inorganic particles 121 to be less than 10 μm, the dispersibility of the inorganic particles 121 is more excellent, and it is possible to effectively prevent the generation of unevenness on the surface of the adhesive layer 12 on the opposite side of the substrate 11, and it is easy to achieve excellent adhesion. In addition, the average particle size of the inorganic particles 121 is measured by laser diffraction scattering method.

[0046] Relative to 100 parts by mass of the adhesive component contained in the adhesive layer 12, the content of the inorganic particles 121 in the adhesive layer 12 is preferably 5 parts by mass or more, particularly preferably 10 parts by mass or more, and further preferably 30 parts by mass or more. In addition, relative to 100 parts by mass of the adhesive component contained in the adhesive layer 12, the content of the inorganic particles 121 in the adhesive layer 12 is preferably 500 parts by mass or less, particularly preferably 250 parts by mass or less, and further preferably 100 parts by mass or less. By making the above content 5 parts by mass or more, the battery adhesive sheet 1 of the present embodiment is easy to exert high insulation. In addition, by making the above content 500 parts by mass or less, when the battery adhesive sheet 1 is heated, the generation of gas from the adhesive layer 12 can be effectively suppressed.

[0047] (2)Adhesive ingredients

[0048] The adhesive component contained in the adhesive layer 12 is not particularly limited, and can be appropriately selected from the perspectives of dissolution into the electrolyte, flame retardancy, heat resistance, insulation, etc. In particular, as the adhesive component, it is preferred to use at least one of acrylic adhesive components, silicone adhesive components, rubber adhesive components, and urethane adhesive components. In addition, the adhesive component contained in the adhesive layer 12 can be any one of an emulsion type, a solvent type, or a solvent-free type, and can also be any one of a cross-linked type or a non-cross-linked type. Among the above, from the perspective of the ease of slight adjustment of the adhesive force, an acrylic adhesive component is preferred, a cross-linked acrylic adhesive component is particularly preferred, and a solvent-type cross-linked acrylic adhesive component is further preferred.

[0049] The acrylic adhesive component is preferably composed of a (meth)acrylate polymer (A) and a crosslinking agent (B). In this case, the adhesive layer 12 contains an acrylic adhesive component composed of a (meth)acrylate polymer (A) and a crosslinking agent (B) and inorganic particles 121. Such an adhesive layer 12 is preferably formed of an adhesive composition containing a (meth)acrylate polymer (A), a crosslinking agent (B) and inorganic particles 121 (hereinafter sometimes referred to as "adhesive composition P").

[0050] In this specification, (meth)acrylate refers to both acrylate and methacrylate. Other similar terms are the same. In addition, "polymer" also includes the concept of "copolymer".

[0051] (2-1) (Meth)acrylate polymer (A)

[0052] From the perspective of making the adhesive layer 12 easily have high adhesion to the adherend, the (meth)acrylate polymer (A) preferably contains an alkyl (meth)acrylate having an alkyl carbon number of 1 to 10 as a monomer unit constituting the polymer. Examples of such alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and n-decyl (meth)acrylate. Among them, alkyl acrylates having an alkyl carbon number of 3 to 9 are preferred, and alkyl acrylates having an alkyl carbon number of 5 to 8 are particularly preferred. These alkyl (meth)acrylates may be used alone or in combination of two or more.

[0053] The (meth)acrylate polymer (A) preferably contains 50% by mass or more, particularly preferably 60% by mass or more, and further preferably 70% by mass or more of a (meth)acrylate alkyl ester having an alkyl group with 1 to 10 carbon atoms as a monomer unit constituting the polymer. By containing 50% by mass or more of the above-mentioned (meth)acrylate alkyl ester, the adhesion to the adherend is further improved. In addition, the (meth)acrylate polymer (A) preferably contains 99% by mass or less, particularly preferably 95% by mass or less, and further preferably 88% by mass or less of a (meth)acrylate alkyl ester having an alkyl group with 1 to 10 carbon atoms as a monomer unit constituting the polymer. By setting the above-mentioned (meth)acrylate alkyl ester to 99% by mass or less, other monomer components can be introduced into the (meth)acrylate polymer (A) in an appropriate amount.

[0054] In addition, from the perspective of making the adhesive layer 12 easily have excellent electrolyte resistance, the (meth)acrylate polymer (A) preferably contains an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms as a monomer unit constituting the polymer. As such an alkyl (meth)acrylate, for example, n-dodecyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, etc. can be cited. Among them, an alkyl (meth)acrylate having an alkyl group with 12 to 18 carbon atoms is preferred. These alkyl (meth)acrylates can be used alone or in combination of two or more.

[0055] The (meth)acrylate polymer (A) preferably contains 0.5% by mass or more, more preferably 4% by mass or more, and particularly preferably 9% by mass or more of an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms as a monomer unit constituting the polymer. By containing 0.5% by mass or more, the obtained adhesive layer 12 has a higher hydrophobicity, thereby easily achieving excellent electrolyte resistance. On the other hand, the (meth)acrylate polymer (A) preferably contains 40% by mass or less, more preferably 30% by mass or less, and particularly preferably 20% by mass or less of an alkyl (meth)acrylate having an alkyl group with 11 to 20 carbon atoms as a monomer unit constituting the polymer. By containing 40% by mass or less of the above-mentioned alkyl (meth)acrylate, it is easy to introduce other monomer components into the (meth)acrylate polymer (A) in an appropriate amount.

[0056] The (meth)acrylate polymer (A) may contain monomers other than those mentioned above as monomer units constituting the polymer as necessary. The monomers may be monomers containing a reactive functional group or monomers not containing a reactive functional group.

[0057] As monomers containing reactive functional groups (monomers containing reactive functional groups), monomers containing carboxyl groups in the molecule (monomers containing carboxyl groups), monomers containing hydroxyl groups in the molecule (monomers containing hydroxyl groups), monomers containing amino groups in the molecule (monomers containing amino groups), etc. can be cited. Among them, the (meth)acrylate polymer (A) preferably contains a hydroxyl-containing monomer or a carboxyl-containing monomer, and particularly preferably contains a carboxyl-containing monomer as a monomer unit constituting the polymer. By containing a carboxyl-containing monomer, the polarity of the formed adhesive layer 12 is increased, and the dissolution resistance to the electrolyte is more excellent.

[0058] As the carboxyl group-containing monomer, for example, ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid can be cited. Among them, acrylic acid is preferred. Acrylic acid can achieve the above-mentioned effect more effectively. The above-mentioned carboxyl group-containing monomers can be used alone or in combination of two or more.

[0059] Examples of the hydroxyl-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. These hydroxyl-containing monomers may be used alone or in combination of two or more.

[0060] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These amino group-containing monomers may be used alone or in combination of two or more.

[0061] The (meth)acrylate polymer (A) preferably contains 0.5% by mass or more, particularly preferably 1% by mass or more, and further preferably 3% by mass or more of a monomer containing a reactive functional group as a monomer unit constituting the polymer. In addition, the (meth)acrylate polymer (A) preferably contains 30% by mass or less, particularly preferably 20% by mass or less, and further preferably 9% by mass or less of a monomer containing a reactive functional group as a monomer unit constituting the polymer. If the (meth)acrylate polymer (A) contains a monomer containing a reactive functional group as a monomer unit in the above amount, a cross-linked structure is well formed by reaction with the cross-linking agent (B), and the cohesive force of the formed adhesive layer 12 is moderately increased, thereby having better resistance to dissolution of the electrolyte.

[0062] On the other hand, examples of monomers not containing a reactive functional group include (meth) alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, (meth) acrylate N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, (meth) acrylates having a non-crosslinkable tertiary amino group such as (meth) morpholine, (meth) acrylamide, dimethylacrylamide, vinyl acetate, styrene, etc. These monomers not containing a reactive functional group may be used alone or in combination of two or more.

[0063] The (meth)acrylate polymer (A) can be obtained by solution polymerization, can be polymerized in the absence of a solvent, or can be obtained by emulsion polymerization. Among them, a solution polymer obtained by solution polymerization is preferred. By making it a solution polymer, it is easy to obtain a linear high molecular weight polymer, which is easy to make the electrolyte resistance of the adhesive layer 12 more excellent.

[0064] The polymerization form of the (meth)acrylate polymer (A) may be a random copolymer or a block copolymer.

[0065] The lower limit of the weight average molecular weight of the (meth)acrylate polymer (A) is preferably 50,000 or more, more preferably 100,000 or more, particularly preferably 200,000 or more, and further preferably 500,000 or more. If the lower limit of the weight average molecular weight of the (meth)acrylate polymer (A) is the above value, the formed adhesive layer 12 has better resistance to dissolution of the electrolyte.

[0066] In addition, the upper limit of the weight average molecular weight of the (meth) acrylate polymer (A) is preferably 2.5 million or less, more preferably 2 million or less, particularly preferably 1.2 million or less, and further preferably 950,000 or less. If the upper limit of the weight average molecular weight of the (meth) acrylate polymer (A) is the above value, the adhesion to the adherend becomes more excellent. In addition, the weight average molecular weight in this specification is a value converted to standard polystyrene measured by gel permeation chromatography (GPC).

[0067] In the adhesive composition P, the (meth)acrylate polymer (A) may be used alone or in combination of two or more.

[0068] (2-2) Cross-linking agent (B)

[0069] As the crosslinking agent (B), any crosslinking agent that reacts with the reactive functional group of the (meth)acrylate polymer (A) may be used, and examples thereof include isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, and ammonium salt crosslinking agents. The crosslinking agent (B) may be used alone or in combination of two or more.

[0070] Among the above, isocyanate crosslinking agents are preferably used from the viewpoints of reactivity with reactive functional groups of the (meth)acrylate polymer (A), particularly with carboxyl groups derived from carboxyl group-containing monomers, and electrolyte resistance and insulating properties after the reaction.

[0071] The isocyanate crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as toluene diisocyanate, diphenylmethane diisocyanate, and xylene diisocyanate; aliphatic polyisocyanates such as hexamethylene diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate; and their biuret bodies and isocyanurate bodies; and adducts as reactants with low molecular weight active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among them, from the perspective of reactivity with hydroxyl groups, trimethylolpropane-modified aromatic polyisocyanates are preferred, and trimethylolpropane-modified toluene diisocyanate and trimethylolpropane-modified xylene diisocyanate are particularly preferred.

[0072] Relative to 100 parts by mass of (meth)acrylate polymer (A), the lower limit of the content of the crosslinking agent (B) in the adhesive composition P is preferably 0.1 parts by mass or more, particularly preferably 0.5 parts by mass or more, and more preferably 1 parts by mass or more. In addition, the upper limit of the content is preferably 20 parts by mass or less, particularly preferably 15 parts by mass or less, and more preferably 10 parts by mass or less. If the content of the crosslinking agent (B) is within the above range, a crosslinked structure can be formed well, and the cohesive force of the formed adhesive layer 12 is moderately increased, thereby becoming more excellent in resistance to dissolution of the electrolyte.

[0073] (2-3) Various additives

[0074] The adhesive composition P may contain various additives generally used in acrylic adhesives, such as tackifiers, antioxidants, softeners, fillers, etc. The additives constituting the adhesive composition P are not included in the polymerization solvent or dilution solvent described below.

[0075] (3) Preparation of Adhesive Composition P

[0076] The adhesive composition P can be prepared by preparing a (meth)acrylate polymer (A), adding the inorganic fine particles 121 to the obtained (meth)acrylate polymer (A), and adding a crosslinking agent (B), additives, etc. as needed.

[0077] The (meth)acrylate polymer (A) can be prepared by polymerizing a mixture of monomers constituting the polymer using a common free radical polymerization method. The polymerization of the (meth)acrylate polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as required. However, the present invention is not limited thereto, and polymerization can also be carried out in the absence of a solvent. As a polymerization solvent, for example, ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc. can be listed, and two or more thereof can also be used simultaneously.

[0078] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more thereof may be used simultaneously. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azo-bis-(2,4-dimethyl-4-methoxyvaleronitrile), 2,2'-azobis(2-methylpropionic acid) dimethyl ester, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0079] Examples of the organic peroxide include benzoyl peroxide, tert-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl) peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, (3,5,5-trimethylhexanoyl) peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0080] Furthermore, in the above-mentioned polymerization step, by adding a chain transfer agent such as 2-mercaptoethanol, the weight average molecular weight of the obtained polymer can be adjusted.

[0081] After the (meth)acrylate polymer (A) is obtained, the inorganic fine particles 121 and, if necessary, the crosslinking agent (B), additives, etc. are added to the solution of the (meth)acrylate polymer (A), and the mixture is thoroughly mixed to obtain an adhesive composition P.

[0082] In addition, in order to adjust the viscosity suitable for coating and adjust the adhesive layer 12 to a desired film thickness, in addition to the above-mentioned polymerization solvent, a diluent solvent or the like may be appropriately used to dilute the adhesive composition P to prepare a coating solution described later. Examples of the diluent solvent include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, and the like, and two or more thereof may be used simultaneously.

[0083] (4) Crosslinking of Adhesive Composition P

[0084] When the adhesive composition P contains a crosslinking agent (B), the adhesive layer 12 can be formed by crosslinking the adhesive composition P. The crosslinking of the adhesive composition P can usually be carried out by heat treatment. In addition, the drying process when the diluting solvent or the like is volatilized from the coating film of the adhesive composition P applied on the desired object can also be used as the heat treatment.

[0085] The heating temperature of the heat treatment is preferably 50 to 150° C., particularly preferably 70 to 120° C. The heating time is preferably 30 seconds to 10 minutes, particularly preferably 50 seconds to 5 minutes.

[0086] After the heat treatment, a 1-2 week aging period may be provided at room temperature (e.g., 23° C., 50% RH) as required. If the aging period is required, the adhesive layer 12 is formed after the aging period. If the aging period is not required, the adhesive layer 12 is formed after the heat treatment is completed.

[0087] (5) Thickness of adhesive layer

[0088] The lower limit of the thickness of the adhesive layer 12 (the value measured based on JIS K7130) is preferably 1 μm or more, particularly preferably 3 μm or more, and more preferably 5 μm or more. By setting the lower limit of the thickness of the adhesive layer 12 to the above value, the adhesive sheet 1 for the battery can easily exert high insulation. In addition, the upper limit of the thickness of the adhesive layer 12 is preferably 50 μm or less, particularly preferably 13 μm or less, and more preferably 9 μm or less. By setting the upper limit of the thickness of the adhesive layer 12 to the above value, the amount of electrolyte immersed from the end of the adhesive layer 12 can be effectively reduced.

[0089] In addition, the thickness of the adhesive layer 12 is preferably 1.1 times or more of the average particle size of the inorganic particles 121, more preferably 5 times or more, particularly preferably 10 times or more, and further preferably 15 times or more. By making the thickness of the adhesive layer 12 more than 1.1 times the average particle size of the inorganic particles 121, the smoothness of the surface of the adhesive layer 12 is more excellent, and high adhesion can be effectively obtained. In addition, the upper limit of the ratio of the thickness of the adhesive layer 12 based on the average particle size of the inorganic particles 121 is not particularly limited, but is preferably 100 times or less, more preferably 60 times or less, and particularly preferably 30 times or less.

[0090] 1-3. Peel off sheet

[0091] The release sheet 13 protects the adhesive layer 12 until the adhesive sheet 1 for a battery is used, and is peeled off when the adhesive sheet 1 for a battery is used. In the adhesive sheet 1 for a battery of the present embodiment, the release sheet 13 is not essential.

[0092] As the release sheet 13, for example, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, polymethylpentene film, polyvinyl chloride film, vinyl chloride copolymer film, polyethylene terephthalate film, polyethylene naphthalate film, polybutylene terephthalate film, polyurethane film, ethylene vinyl acetate film, ionomer resin film, ethylene-(methyl) acrylic acid copolymer film, ethylene-(methyl) acrylic acid ester copolymer film, polystyrene film, polycarbonate film, polyimide film, fluororesin film, liquid crystal polymer film, etc. can be used. In addition, crosslinked films of these films can also be used. Further, laminated films of these films can also be used.

[0093] The release surface (surface in contact with the adhesive layer 12) of the release sheet 13 is preferably subjected to a release treatment. Examples of release agents used for the release treatment include alkyd, silicone, fluorine, unsaturated polyester, polyolefin, and wax release agents.

[0094] The thickness of the release sheet 13 is not particularly limited, but is generally about 20 to 150 μm.

[0095] 2. Physical properties of adhesive sheets for batteries

[0096] (1) Gas generation

[0097] In the adhesive sheet 1 for batteries of the present embodiment, the amount of gas (gas generation) generated by heating per 1g of inorganic particles is preferably less than 30ml / g, particularly preferably less than 10ml / g, and further preferably less than 3ml / g. By making the gas generation less than 30ml / g, even when the battery manufactured using the adhesive sheet 1 for batteries is heated, the expansion of the battery can be effectively suppressed. In the adhesive sheet 1 for batteries of the present embodiment, by using inorganic particles 121 having the above-mentioned water content as the particles contained in the adhesive layer 12, the gas generation caused by heating can be suppressed within the above-mentioned range. In addition, for the lower limit of the above-mentioned gas generation, although it is preferred that no gas (0ml / g) is generated, when gas is generated, it can be, for example, more than 0.1ml / g, and in particular more than 1ml / g. In addition, the details of the method for determining the above-mentioned gas generation are shown in the test examples described later.

[0098] (2) Adhesion

[0099] The lower limit of the adhesion of the battery adhesive sheet 1 to the aluminum plate of the present embodiment is preferably 0.5N / 25mm or more, more preferably 0.8N / 25mm or more, and particularly preferably 1.5N / 25mm or more. By setting the lower limit of the adhesion of the battery adhesive sheet 1 to the above value, it is not easy to produce the undesirable condition that the battery adhesive sheet 1 is peeled off from the adherend (especially the metal component). The upper limit of the above-mentioned adhesion is not particularly limited, but it is generally preferably 50N / 25mm or less, particularly preferably 30N / 25mm or less, and further preferably 9N / 25mm or less. In addition, the adhesion in this specification basically refers to the adhesion measured by the 180° peeling method based on JIS Z0237:2009, and the detailed measurement method is shown in the test example described later.

[0100] (3) Insulation (based on the temperature rise of the forced internal short-circuit test)

[0101] For the adhesive sheet 1 for the battery (excluding the peeling sheet 13), when a small nickel sheet of standard size (height 0.2mm, width 0.1mm, L-shaped with one side of 1mm, angle 90°) is used, the temperature rise of the battery side during the forced internal short circuit test of the battery according to JIS C8714:2007 is preferably 30°C or less, more preferably 10°C or less, particularly preferably 5°C or less, and further preferably less than 1°C. In addition, when a small nickel sheet of a size larger than the standard size (height 0.5mm, width 0.2mm, L-shaped with one side of 3mm, angle 90°) is used, the above-mentioned temperature rise is preferably 100°C or less, more preferably 30°C or less, particularly preferably 10°C or less, and further preferably 4°C or less. The details of the forced internal short circuit test are shown in the test examples described later.

[0102] By setting the temperature rise based on the forced internal short circuit test to the above value, the battery adhesive sheet 1 can have higher insulation, and the battery using the battery adhesive sheet 1 has higher safety. In particular, the battery adhesive sheet 1 of this embodiment uses the above-mentioned sulfate particles as the inorganic particles 121, which makes it easy to suppress the temperature rise based on the forced internal short circuit test to a low level as described above.

[0103] (4) Thickness of battery adhesive sheet

[0104] The thickness of the adhesive sheet 1 for the battery (excluding the thickness of the peeling sheet 13) is preferably 10 μm or more, particularly preferably 15 μm or more, and more preferably 20 μm or more. In addition, the thickness of the adhesive sheet 1 for the battery is preferably 250 μm or less, particularly preferably 110 μm or less, and more preferably 45 μm or less. By making the thickness of the adhesive sheet 1 for the battery within the above range, it is easy to take into account both excellent adhesion and high insulation.

[0105] 3. Method for manufacturing adhesive sheet for battery

[0106] As the manufacturing method of the adhesive sheet 1 for batteries of the present embodiment, as long as the adhesive layer 12 can be formed on one side of the substrate 11, there is no particular limitation. For example, a coating liquid containing the above-mentioned adhesive composition P and a desired solvent is applied to the release surface of the release sheet 13, and a heat treatment is performed to form a coating film. When a aging period is not required, the formed coating film directly becomes the adhesive layer 12. When a aging period is required, the formed coating film becomes the adhesive layer 12 after the aging period. The conditions for heating treatment and aging are as described above. Then, one surface of the substrate 11 is attached to the surface of the formed coating film or adhesive layer 12 on the opposite side of the release sheet 13, and after the aging period is set as needed, the adhesive sheet 1 for batteries can be obtained.

[0107] The drying treatment when the diluting solvent of the coating liquid is volatilized can also be used as the above-mentioned heat treatment. When the heat treatment is performed, the heating temperature is preferably 50 to 150° C., and particularly preferably 70 to 120° C. In addition, the heating time is preferably 30 seconds to 10 minutes, and particularly preferably 50 seconds to 2 minutes. After the heat treatment, a aging period of about 1 to 2 weeks can be set at room temperature (e.g., 23° C., 50% RH) as needed.

[0108] In addition, as another method for manufacturing the adhesive sheet 1 for a battery of the present embodiment, the adhesive composition P is applied to the substrate 11, and then the adhesive layer 12 is formed on the substrate 11, thereby obtaining the adhesive sheet 1 for a battery. In this case, the application, heating treatment and aging of the adhesive composition P can be performed in the same manner as the above method.

[0109] [Lithium-ion battery]

[0110] A lithium ion battery according to one embodiment of the present invention uses the above-mentioned battery adhesive sheet inside the battery to fix two or more conductors in a state of contact with each other. Preferably, at least one of the two or more conductors is in sheet form, and at least one is in wire or strip form. The lithium ion battery according to the preferred embodiment is described below.

[0111] like Figure 2 As shown, the lithium ion battery 2 of this embodiment includes: a bottomed cylindrical outer casing 21 having a negative terminal 23 at the bottom, a positive terminal 22 provided at an opening of the outer casing 21, and an electrode body 24 provided inside the outer casing 21. In addition, an electrolyte is sealed inside the lithium ion battery 2.

[0112] The electrode body 24 has a sheet-shaped (belt-shaped) positive electrode collector 241 on which a positive electrode active material layer 241a is stacked, a negative electrode collector 242 on which a negative electrode active material layer 242a is stacked, and a separator 243 between the positive electrode collector 241 and the negative electrode collector 242. In addition, the stack of the positive electrode collector 241 and the positive electrode active material layer 241a is sometimes referred to as a positive electrode, and the stack of the negative electrode collector 242 and the negative electrode active material layer 242a is sometimes referred to as a negative electrode, and the positive electrode and the negative electrode are collectively referred to as electrodes. The positive electrode, the negative electrode, and the separator 243 are respectively wound and inserted into the interior of the outer body 21.

[0113] In addition, if Figure 3 As shown, a linear or strip-shaped electrode lead tab 244 is attached to the positive electrode current collector 241 through the above-mentioned battery adhesive sheet 1, thereby, the electrode lead tab 244 is electrically connected to the positive electrode current collector 241. The electrode lead tab 244 is also electrically connected to the above-mentioned positive electrode terminal 22. In addition, the negative electrode current collector 242 is electrically connected to the negative electrode terminal 23 via an electrode lead tab not shown.

[0114] Typically, the positive electrode current collector 241 and the negative electrode current collector 242 are made of metal such as aluminum, and the electrode lead tab 244 is made of metal such as aluminum or copper.

[0115] The electrolyte used in the lithium ion battery 2 is usually a non-aqueous electrolyte. As the non-aqueous electrolyte, for example, an electrolyte obtained by dissolving a lithium salt as an electrolyte in a mixed solvent of a cyclic carbonate and a low-order chain carbonate can be preferably cited. As the lithium salt, fluorine complex salts such as lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4) or LiN(SO2Rf)2·LiC(SO2Rf)3 (wherein, Rf=CF3, C2F5) can be used. In addition, as the cyclic carbonate, ethylene carbonate, propylene carbonate, etc. can be used, and as the low-order chain carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, etc. can be preferably cited.

[0116] The lithium ion battery 2 of the present embodiment can be manufactured by a common method except that the above-mentioned adhesive sheet 1 for a battery is used for fixing the electrode extraction tab 244 .

[0117] In the lithium ion battery 2 of the present embodiment, the electrode lead-out tab 244 is attached to the positive electrode collector 241 by the battery adhesive sheet 1. By making the adhesive layer 12 contain inorganic particles 121, the battery adhesive sheet 1 can achieve high insulation. Furthermore, by making the inorganic particles 121 have the above-mentioned water content, even when the lithium ion battery 2 is heated, the generation of gas inside the battery can be suppressed, and the occurrence of undesirable conditions such as swelling of the lithium ion battery 2 can be suppressed. In summary, the lithium ion battery 2 of the present embodiment can exert excellent performance.

[0118] The embodiments described above are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above embodiments also covers all design changes or equivalents within the scope of protection of the present invention.

[0119] For example, the release sheet 13 may be omitted in the adhesive sheet for a battery 1. In addition, another layer may be provided between the base material 11 and the adhesive layer 12 in the adhesive sheet for a battery 1.

[0120] Example

[0121] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.

[0122] [Example 1]

[0123] 1. Preparation of coating solution of adhesive composition

[0124] A (meth)acrylate polymer was prepared by copolymerizing 80 parts by mass of 2-ethylhexyl acrylate, 15 parts by mass of dodecyl methacrylate, and 5 parts by mass of acrylic acid by solution polymerization. The molecular weight of the polymer was measured by gel permeation chromatography (GPC) as described below, and the weight average molecular weight (Mw) was 750,000.

[0125] Then, 100 parts by mass (solid content conversion value; the same below) of the obtained (meth)acrylate polymer and 3.72 parts by mass of trimethylolpropane-modified toluene diisocyanate (manufactured by TOYOCHEM Co., Ltd., trade name "BHS8515") as an isocyanate crosslinking agent were mixed and diluted with ethyl acetate to prepare a dilution having a solid content concentration of 30%. The dilution contained the above-mentioned (meth)acrylate polymer and the above-mentioned isocyanate crosslinking agent as adhesive components.

[0126] To 100 parts by mass of the adhesive component, 50 parts by mass of barium sulfate fine particles (manufactured by Sakai Chemical Industry Co., Ltd., product name "B-55", average particle size: 0.6 μm) as inorganic fine particles were added and mixed to obtain a coating liquid of an adhesive composition.

[0127] 2. Formation of adhesive layer

[0128] The coating liquid of the adhesive composition obtained in the above step 1 was applied to the release-treated surface of a release sheet (manufactured by Lintec Corporation, trade name "SP-PET251130") on one side of a polyethylene terephthalate film subjected to release treatment using a silicone release agent using a knife coater, and the obtained coating was dried at 120° C. for 1 minute to form an adhesive layer having a thickness of 9 μm. Thus, a laminate consisting of the release sheet and the adhesive layer was obtained.

[0129] 3. Production of adhesive sheets for batteries

[0130] The surface on the adhesive layer side of the laminate obtained in the above step 2 is bonded to one surface of a polyimide film (manufactured by DUPONT-TORAY Co., Ltd., trade name "KAPTO 100H", thickness: 25 μm, flame retardant grade according to UL94 standard: V-0) as a substrate, and then aged at 23°C and 50% RH for 7 days to obtain an adhesive sheet for a battery in which a substrate, an adhesive layer and a release sheet are laminated in sequence.

[0131] The weight average molecular weight (Mw) is a weight average molecular weight in terms of standard polystyrene measured using gel permeation chromatography (GPC) under the following conditions (GPC measurement).

[0132] <Measurement conditions>

[0133] ·GPC measuring apparatus: manufactured by TOSOH CORPORATION, HLC-8320

[0134] ·GPC columns (passed in the following order): manufactured by TOSOH CORPORATION

[0135] TSK gel super HH

[0136] TSK gel super HM-H

[0137] TSK gel super H2000

[0138] ·Test solvent: tetrahydrofuran

[0139] ·Measurement temperature: 40℃

[0140] [Examples 2 to 7, Comparative Examples 1 to 4]

[0141] An adhesive sheet for a battery was produced in the same manner as in Example 1 except that the type and addition amount of the inorganic fine particles were changed as shown in Table 1. In addition, the description "-" in Comparative Example 6 means that no fine particles were used.

[0142] [Test Example 1] (Measurement of water content)

[0143] The water content (%) of the inorganic fine particles used in the examples and comparative examples was measured using a coulometric Karl Fischer moisture meter (manufactured by KYOTO ELECTRONICS MANUFACTURING CO., LTD., product name "MKC-510N"). In this measurement, the heating temperature was set to 150°C, "Aquamicron AX" manufactured by Mitsubishi Chemical Corporation was used as the anolyte (generating solution), and "Aquamicron CXU" manufactured by Mitsubishi Chemical Corporation was used as the catholyte (counteractive solution).

[0144] [Test Example 2] (Measurement of Adhesive Strength)

[0145] The adhesive strength of the adhesive sheet for a battery in this test example was measured in accordance with JIS Z0237:2009 except for the following operation.

[0146] After cutting the adhesive sheet for the battery obtained in the embodiment and the comparative example into a width of 25 mm and a length of 250 mm, peel off the peeling sheet to obtain a test piece. Using a 2kg rubber roller, the adhesive layer exposed by the test piece is attached to an aluminum plate as an adherend at 23°C and 50% RH. Then, immediately use a universal tensile testing machine (manufactured by ORIENTEC CORPORATION, product name "TENSILON UTM-4-100") to peel off the test piece from the above-mentioned aluminum plate at a peeling angle of 180° and a peeling speed of 300 mm / min, thereby measuring the adhesion (N / 25mm). The results are shown in Table 1.

[0147] [Test Example 3] (Evaluation of Gas Generation Amount)

[0148] The peeling sheet was peeled off from the battery adhesive sheet obtained in the embodiment and the comparative example, and the exposed surface of the exposed adhesive layer was attached to the aluminum foil, and then the test piece was cut into 10 mm wide and 30 mm long. After the test piece and the electrolyte were sealed in an aluminum-plastic composite bag in an inert gas atmosphere, the opening of the bag was sealed by heat sealing. As the electrolyte, lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solution of ethylene carbonate and diethyl carbonate at a volume ratio of 1:1 at a concentration of 1 mol / L.

[0149] After sealing, the aluminum-plastic composite bag was taken out from the inert gas atmosphere, and its volume (ml) was measured using an electronic densimeter (manufactured by Alfa Mirage Co., Ltd., product name "MD-200S"). The volume thus measured was set as the initial volume.

[0150] Next, the sealed aluminum-plastic composite bag was heated at 85° C. for 72 hours, and then the volume (ml) was measured again in the same manner as above. The volume thus measured was defined as the volume after heating.

[0151] The initial volume and the volume after heating obtained as described above, and the value (g) obtained by calculating the mass of the fine particles contained in the adhesive layer of the test piece were substituted into the following formula (1) to calculate the amount of gas generation (ml / g).

[0152] Gas generation (ml / g) = {volume after heating (ml) - initial volume (ml)} / {mass of particles (g)} ... (1)

[0153] [Test Example 4] (Evaluation of battery insulation properties)

[0154] (1) Preparation of positive electrode

[0155] 100 parts by mass of LiNi 0.82 Co 0.15 Al 0.03 O2, 1.0 parts by mass of acetylene black, 0.9 parts by mass of polyvinylidene fluoride (binder), and an appropriate amount of NMP are mixed to prepare a positive electrode paste. The obtained positive electrode paste is evenly coated on both sides of an aluminum foil with a thickness of 20 μm as a positive electrode collector, and after drying, it is rolled to produce a strip positive electrode with a width of 58 mm. Among them, on both sides of the outermost peripheral ends in the long side direction of the positive electrode, there is an exposed portion of the aluminum foil exposed from one end to the other end in the width direction of the positive electrode collector. At this time, the width W of the exposed portion is set to 60 mm.

[0156] Then, a strip-shaped aluminum positive electrode lead with a width of 3.5 mm and a length of 68 mm was stacked at a position 3 mm away from the outermost edge of the exposed portion of the positive electrode collector, aligned so that the length of the extraction portion was 15 mm and the length of the overlapping portion was 53 mm, and the overlapping portion was welded to the exposed portion.

[0157] Then, the battery adhesive sheet obtained in the embodiment and the comparative example was attached to the positive electrode in such a manner that the entire surface of the exposed portion and the entire surface of the repeated portion were covered. At this time, the battery adhesive sheet was exposed 2 mm from each end of the width direction of the positive electrode in such a manner that the exposed portion was surely covered by the battery adhesive sheet. In addition, on the positive electrode active material layer, the battery adhesive sheet was also exposed 2 mm from the end of the width direction of the exposed portion.

[0158] (2) Preparation of negative electrode

[0159] 100 parts by mass of flaky artificial graphite with an average particle size of about 20 μm as a negative electrode active material, 1 part by mass of styrene-butadiene rubber (SBR) (binder), 1 part by mass of carboxymethyl cellulose (thickener) and water are mixed to prepare a negative electrode paste. The obtained negative electrode paste is evenly coated on both sides of a copper foil with a thickness of 8 μm as a negative electrode collector, and after drying, it is rolled to produce a strip-shaped negative electrode with a width of 59 mm. Among them, on both sides of the end of the winding end side of the negative electrode, there is an exposed portion that is exposed from one end to the other end in the width direction of the negative electrode collector.

[0160] Then, a strip-shaped nickel negative electrode lead having a width of 3 mm and a length of 40 mm was stacked on the exposed portion of the negative electrode current collector, aligned in the same manner as the positive electrode, and the overlapping portion was welded to the exposed portion.

[0161] (3) Preparation of electrode group

[0162] The positive electrode and negative electrode obtained above are stacked and wound with a separator interposed therebetween to form an electrode group. At this time, the lead of the positive electrode is made to protrude from one end face of the electrode group, and the lead of the negative electrode is made to protrude from the other end face.

[0163] (4) Preparation of non-aqueous electrolyte

[0164] LiPF6 was dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate (volume ratio 1:1:8) so that the concentration of LiPF6 was 1.4 mol / L to prepare a non-aqueous electrolyte.

[0165] (5) Battery production

[0166] An electrode group clamped by a lower insulating ring and an upper insulating ring is housed in an iron battery box (18 mm in diameter and 65 mm in height) with nickel plating on the inner surface. At this time, the negative lead is placed between the lower insulating ring and the bottom of the battery box. In addition, the positive lead is passed through the through hole in the center of the upper insulating ring. Then, the electrode rod is passed through the hollow portion in the center of the electrode group and the through hole in the center of the lower insulating ring, and one end of the negative lead is welded to the inner bottom surface of the battery box. In addition, one end of the positive lead pulled out from the through hole of the upper insulating ring is welded to the inner surface of a sealing plate having a sealing gasket on the peripheral portion. Then, a groove is made near the opening of the battery box, and a non-aqueous electrolyte is injected into the battery box to impregnate the electrode group. Then, the opening of the battery case was sealed with a sealing plate, and the open end of the battery case was sealed (sealed) to the peripheral edge of the sealing plate via a sealing gasket to obtain a cylindrical nonaqueous electrolyte secondary battery (energy density 600Wh / L).

[0167] (6) Implementation of mandatory internal short-circuit test

[0168] Using the non-aqueous electrolyte secondary battery obtained above, a forced internal short circuit test of the battery was performed based on JIS C8714:2007. As small nickel sheets, small nickel sheets of standard size (height 0.2mm, width 0.1mm, L-shaped with one side of 1mm, angle 90°) and small nickel sheets larger than the standard size (height 0.5mm, width 0.2mm, L-shaped with one side of 3mm, angle 90°) were prepared. The above-mentioned small nickel sheets are arranged between the battery adhesive sheet and the diaphragm in such a way that these small nickel sheets penetrate the battery adhesive sheet. Specifically, a small nickel sheet is arranged on the battery adhesive sheet located in the central part of the width direction of the positive electrode collector and 5mm away from the end of the positive electrode active material layer when viewed from above. A forced internal short circuit test was then performed, and the rising temperature (°C) of the side of the battery was measured by thermoelectric pairs. The results are shown in Table 1.

[0169] [Test Example 5] (Evaluation of electrolyte resistance)

[0170] After cutting the adhesive sheet for the battery obtained in the embodiment and the comparative example into a width of 11 mm and a length of 30 mm, peel off the peeling sheet. Then, under an environment of 23°C and 50% RH, use a 2kg rubber roller to attach the exposed adhesive layer to an aluminum plate as an adherend, and use it as a test piece. The test piece is sealed in an aluminum-plastic composite bag together with an electrolyte and heated at 80°C for 3 days. As the electrolyte, a preparation liquid is prepared by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1 mol / L in a mixed solution of ethylene carbonate and diethyl carbonate mixed in a volume ratio of 1:1. Then, take out the test piece, peel off the adhesive sheet for the battery from the aluminum plate with tweezers, and confirm the ease of peeling off at this time. In addition, the electrolyte resistance is evaluated based on the following judgment criteria. The results are shown in Table 1.

[0171] 3 ...Peeling at the interface between the adhesive layer and the adherend.

[0172] 2…The adhesive layer swells, causing cohesive failure or transfer.

[0173] 1…Peel off in an aluminum-plastic composite bag.

[0174] In addition, the details of the abbreviations and the like described in Table 1 are as follows.

[0175] [particle]

[0176] Barium sulfate 1: barium sulfate fine particles (manufactured by Sakai Chemical Industry Co., Ltd., product name "B-55", average particle size: 0.6 μm)

[0177] Barium sulfate 2: barium sulfate fine particles (manufactured by Sakai Chemical Industry Co., Ltd., product name "BB-02", average particle size: 0.3 μm)

[0178] Titanium dioxide 1: Titanium dioxide fine particles (manufactured by Sakai Chemical Industry Co., Ltd., product name "R-310", average particle size: 0.2 μm)

[0179] Aluminum hydroxide: Aluminum hydroxide fine particles (manufactured by Nippon Light Metal Company, Ltd., product name "BF013", average particle size: 1.2 μm)

[0180] Alumina: Alumina fine particles (manufactured by Denka Company Limited., product name "ASFP-20", average particle size: 0.26 μm)

[0181] Magnesium carbonate: Magnesium carbonate fine particles (manufactured by KONOSHIMA Co., LTD, product name "MSS", average particle size: 1.2 μm)

[0182] Titanium dioxide 2: Titanium dioxide fine particles (manufactured by Sakai Chemical Industry Co., Ltd., product name "STR-100N", average particle size: 0.015 μm)

[0183] Titanium dioxide 3: Titanium dioxide fine particles (manufactured by ISHIHARA SANGYO KAISHA, LTD., product name "R630", average particle size: 0.24 μm)

[0184] Magnesium oxide: Magnesium oxide fine particles (manufactured by KONOSHIMA Co., LTD, product name "PSF-150", average particle size: 0.60 μm)

[0185] [Table 1]

[0186]

[0187] As shown in Table 1, the battery adhesive sheets of the embodiments are not easy to generate gas even when placed in a high temperature environment. In addition, the battery adhesive sheets of some embodiments can suppress the temperature rise based on the forced internal short circuit test to a small level and have high insulation properties. In addition, the battery adhesive sheets of the embodiments have good electrolyte resistance.

[0188] Industrial Applicability

[0189] The adhesive composition and the adhesive sheet for a battery of the present invention are suitable for use inside a lithium ion battery, and are particularly suitable for attaching an electrode extraction tab to an electrode.

Claims

1. An adhesive sheet for a battery, comprising a substrate and an adhesive layer provided on one surface side of the substrate, wherein the adhesive sheet for a battery is characterized in that: The adhesive layer comprises an adhesive component and inorganic fine particles having a water content of 0.4% or less when used alone. The inorganic particles are sulfate particles, The adhesive component is an acrylic adhesive component composed of a (meth)acrylate polymer (A) and a crosslinking agent (B). The adhesive force of the adhesive sheet for a battery to the aluminum plate is 0.5 N / 25 mm or more and 50 N / 25 mm or less.

2. The adhesive sheet for a battery according to claim 1, wherein The sulfate particles are barium sulfate particles.

3. The adhesive sheet for a battery according to claim 1, wherein The content of the inorganic fine particles in the adhesive layer is 5 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the adhesive component contained in the adhesive layer.

4. The adhesive sheet for a battery according to claim 1, wherein The inorganic fine particles have an average particle size of 0.01 μm or more and 10 μm or less.

5. A lithium ion battery, characterized in that: Inside the battery, use a battery adhesive sheet to fix the positive electrode and the positive lead in contact with each other. The adhesive sheet for a battery includes a substrate and an adhesive layer provided on one surface side of the substrate. The adhesive layer comprises inorganic fine particles having a water content of 0.4% or less when used alone, The inorganic particles are sulfate particles.

6. The lithium-ion battery according to claim 5, characterized in that: The adhesive layer contains an acrylic adhesive component composed of a (meth)acrylate polymer (A) and a crosslinking agent (B).

7. The lithium-ion battery according to claim 5, characterized in that: The adhesive force of the adhesive sheet for a battery to the aluminum plate is 0.5 N / 25 mm or more and 50 N / 25 mm or less.

8. The lithium-ion battery according to claim 5, characterized in that: The sulfate particles are barium sulfate particles.

9. The lithium-ion battery according to claim 5, characterized in that: The content of the inorganic fine particles in the adhesive layer is 5 parts by mass or more and 500 parts by mass or less relative to 100 parts by mass of the adhesive component contained in the adhesive layer.

10. The lithium ion battery according to claim 5, characterized in that: The inorganic fine particles have an average particle size of 0.01 μm or more and 10 μm or less.

Citation Information

Patent Citations

  • Nonaqueous electrolytic secondary battery

    WO2017038010A1

  • Ceramic diaphragm, lithium ion battery and preparation methods for ceramic diaphragm and lithium ion battery

    CN106684289A

  • Insulating tape

    JP2017152372A

  • Slurry for lithium ion secondary battery porous film, production method therefor, separator for lithium ion secondary battery, and lithium ion secondary battery

    WO2014148577A1

  • Separator for battery-use

    WO2018021143A1